A programmable molecular robot. - Muscat, R; Bath, J; Turberfield, A (2011)
We have developed a programmable and auton-omous molecular robot whose motion is fueled by DNA hybridization. Instructions determining the path to be followed are programmed into the fuel molecules, allowing precise control of cargo motion on a branched track.